Strategi Social Media Engagement dalam Meningkatkan Penjualan Produk pada Rumah Makan Cinla di Cililitan Jakarta Timur - Widya Nuriyanti; Delia Milla Vernia; Husain Nurisman; Loecita Sandiar; Cindy Amara Yapi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to find out what social media strategies will increase audience engagement on social media and increase product sales at Cinla Restaurant. The method used is qualitative, by means of observation, documentation and interviews. The population in this study are consumers of Cinla Restaurant in Cililitan, East Jakarta. Based on the results of the study, it can be concluded that a social media engagement strategy that can increase product sales is to create content that can attract audience involvement, follow trending content, and pay attention to market conditions in order to find out consumer desires for products so that they can increase sales volume.